A Perceiving-making forests with work tables in times of ruins and precariousness (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
In times of ruin and precariousness (Tsing, 2019, 2022), we seek to explore a fabled path with “work tables”, a device for collective artistic creation that seeks to perceive and create forests by inventing themselves in the company of more-than-human beings, such as birds, viruses, plants, and frogs. We focused on reflecting on four work tables created during an artistic residency and demonstrating how such relationships with companion species (Haraway, 2021, 2022) foster the activation and engagement of bodies (Greiner, 2017) in symbiotic multispecies performances. The tables presuppose forestry (Krenak, 2022) as a political gesture in the face of the Anthropocene.
Keywords: working table; forest; scientific and cultural communication; multispecies arts; precariousness